2019
DOI: 10.1161/strokeaha.118.022509
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Vessel Wall Lesions on 7T MRI (Magnetic Resonance Imaging)

Abstract: Background and Purpose— Intracranial vessel wall lesions are a novel imaging marker of intracranial atherosclerosis (ICAS), but data on their occurrence and risk factors are lacking. Our aim was to study the frequency, distribution, and risk factors of intracranial vessel wall lesions on 7T magnetic resonance imaging in patients with a history of vascular disease. Methods— Within the SMART-MR study (Second Manifestations of Arterial Disease-Magnetic Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…This is in line with early postmortem studies that reported frequencies approaching 100% in older age. 27,28 Furthermore, the distribution of vessel wall lesions, which we recently reported, 12 was also in line with the distribution of plaques in those postmortem studies, particularly the increased involvement of the larger cerebral arteries compared with the smaller ones. These findings suggest that vessel wall MR imaging at 7T allows a more accurate approximation of the ICAS burden, compared with other neuroimaging methods.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This is in line with early postmortem studies that reported frequencies approaching 100% in older age. 27,28 Furthermore, the distribution of vessel wall lesions, which we recently reported, 12 was also in line with the distribution of plaques in those postmortem studies, particularly the increased involvement of the larger cerebral arteries compared with the smaller ones. These findings suggest that vessel wall MR imaging at 7T allows a more accurate approximation of the ICAS burden, compared with other neuroimaging methods.…”
Section: Discussionsupporting
confidence: 87%
“…Vessel wall MR imaging directly visualizes the pathologic vessel wall, enabling more accurate measurement of the ICAS burden. 11,12,26 A very high frequency of ICAS was found in the current population, 12 especially compared with other neuroimaging studies. This is in line with early postmortem studies that reported frequencies approaching 100% in older age.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations